Determining the form of error distribution of geodetic measuring - Gladilin, Valeriy; Belenok, Vadym; Shudra, Nataliia (Geodesy and Cartography, 2022)
Industrial equipment is a dynamic system and has deformations not only during installation but also during operation. Under the influence of variable load and displacement of the center of gravity, the soil under the foundation settles unevenly, and accordingly, the equipment deforms unevenly, which is a threat to the equipment, the greater the load corresponds to more subsidence. Separation of partial deformations from full is important for determining the elements of straightening equipment for its uninterrupted and trouble-free operation. The presence of significant total deformation does not affect the performance of the equipment. The most critical deformations are partial deformations. Absolute vertical deformations are calculated as the difference in sediment between adjacent sediment marks, which are fixed on the equipment in the same measurement cycle. Comparing the values of deformations with the allowable technical conditions, decide on the need for straightening and adjustment of equipment. The accuracy of installation is characterized by a tolerance of 0.1÷0.5 mm on the relative position of the equipment, which is conjugate mounted at a distance of several tens or hundreds of meters. For installation of the equipment with such accuracy carry out special geodetic works with use of methods and technical means of measurements specially developed for this purpose in geodesy, metrology and mechanical engineering.